Women's Mental Health Services and Pregnancy: A Review. Issue 2 (February 2022) - Ghahremani, Taylor; Magann, Everett F.; Phillips, Amy; Ray-Griffith, Shona L.; Coker, Jessica L.; Stowe, Zackary N.
Abstract : Importance: The importance of women's mental health services is becoming more evident as we learn more about the impact of mental health on maternal and perinatal outcomes. Objective: The purpose of this review is to identify the importance of mental health issues arising during pregnancy including prevention, timely diagnosis and treatment, and referral to specialized services. Evidence Acquisition: A literature search was undertaken using the search engines PubMed, CINAHL, and PsycINFO. The search terms were as follows: "mental health services" or "behavioral health" or "mental health counseling" or "psychological" and "delivery of health care" and "pregnancy" or "pregnant." The years searched were January 2000 to November 2020. The search was limited to English language. Results: Of the 255 abstracts identified and reviewed, 35 full-text articles were the basis of this review. Literature summarizing the availability and models of care for mental health services for pregnant women is limited. After reviewing the literature, the themes of depression and anxiety in the antepartum and postpartum periods that emerged as mental health issues, especially during adolescent pregnancies, the coronavirus pandemic, intimate partner violence, and pregnancy loss, are of primary importance to obstetrical providers. All of these issues can have a significant impact on maternal and neonatal outcomes and should be addressed during routine practice. Conclusions and Relevance: Maternal mental health is garnering deserved attention and has enormous implications on maternal and infant outcomes. Obstetrical providers should be comfortable with screening, identification, and basic treatment algorithms including when to refer to specialized services. Relevance Statement: Mental health issues during pregnancy and the postpartum period can be profound with severe maternal and perinatal consequences. Target Audience: Obstetricians and gynecologists, family physicians, psychiatrists. Learning Objectives: After completing this activity, the learner should be better able to identify the mental health services that are available for pregnant women; outline the common mental illnesses that are present during adolescent pregnancies; explain the risk factors that have been linked with perinatal depression; and describe the management and potential complications of pregnant patients presenting with mental illness.